RANCANG BANGUN LASER UNTUK PEMBELAJARAN OPTIKA DALAM MENENTUKAN INDEKS BIAS DAN DIFRAKSI KISI - Puji Hariati Winingsih (Universitas Sarjanawiyata Tamansiswa, 2015)
This research is executed as a mean to make laser with energy from ex- materials ( DVD) to be used to determine refractive index and difraction. For that, have been made laser diode appliance network used to determine refractive index and laser wavelength [pass/through] difraction. This research is used by analysis with refractive index characteristic and difraction. Obtained result of that level of prism refractive index at variation of i1 (30o, 45o dan 60o) equal to (1.53 ± 0.07), (1.45 ± 0.08) and ( 1.53 ± 0.08). Green Laser wavelength at variation of N (100, 300 and 600 line / mm)successively equal to (500 ± 0.03), (525 ± 0.02) and (541 ± 0.07). Pursuant to prism refractive index theory of[is level of 1.5 and green colour laser wavelength range from (500 – 570) nm. So that can be concluded that result of research have as according to this appliance and theory have earned to be told good to used in study of optics